Structural characterization and inhibition on α-glucosidase activity of acidic polysaccharide from Annona squamosa. (15th October 2017) - Ren, Yuan-yuan; Zhu, Zhen-Yuan; Sun, Hui-qing; Chen, Li-Jing
Highlights: A kind of acidic polysaccharide was isolated from Annona squamosa . Three different methods were used to determine the monosaccharide composition. Methylation, FT-IR and NMR were combined to characterize the structure. The acidic polysaccharide had a certain inhibition activity on α-glucosidase. Abstract: The crude polysaccharide (TASP3) was extracted from the fruit pulp of Annona squamosa and then isolated and purified by the combination of grading-alcoholic precipitation and Sephadex G-200. The structure of purified polysaccharide (GASP3-3-I) was determined based on the physicochemical and instrumental analyses. The results indicated that GASP3-3-I was an acidic heteropolysaccharide and its average molecular weight was 2.28 × 10 6  Da. The monosaccharide composition was analysed by GC–MS and ion chromatography, respectively. It was revealed that GASP3-3-I was consisted of rhamnose, arabinose, xylose, mannose, glucose, galactose, glucuronic acid and galacturonic acid with a molar ratio of 5.06:45.5:5.26:0.63:6.09:31.76:0.49:5.19. Moreover, periodate oxidation reaction, Smith degrading reaction, methylation, FT-IR and NMR were used to conduct the structural characterization of GASP3-3-I. The results indicated that glycosyl residues of GASP3-3-I were mainly composed of (1→)l -arabinose, (1 → 6), (1 → 3) and (1, 3 → 6)d -galactose, (1→)d -xylose, (3→) and (3 → 6)d -glucose, (1 → 2)l -rhamnose. The α-glucosidase inhibitory activity assay showed that GASP3-3-I had a certain inhibition on α-glucosidase activity.